2020
DOI: 10.3389/fnins.2019.01441
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Inhalation Attenuates Oxidative Stress Related Endothelial Cells Injury After Subarachnoid Hemorrhage in Rats

Abstract: Background: Subarachnoid hemorrhage (SAH) is a devastating cerebrovascular disease with poor clinical outcome. Nucleotide binding and oligomerization domainlike receptor family pyrin domain-containing 3 (NLRP3) inflammasome serves a key role in inflammatory response, which may lead to endothelial cell injury and blood-brain barrier (BBB) disruption. Hydrogen (H 2) is considered a neuroprotective antioxidant. This study was set out to explore whether hydrogen inhalation protects against SAH induced endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…During the past decade, many basic and clinical studies have provided evidence supporting the view that H 2 treatment protects against CVD and improves cardiac function. Ohsawa et al discovered that consumption of HW for 6 months reduced the oxidative stress level and the volume of atherosclerotic lesions derived from macrophage accumulation in apolipoprotein E knockout mice (ApoE-/- mice) [ 87 ]. Iketani et al recently revealed that continuous administration of HW in low-density lipoprotein (LDL) receptor-deficient mice decreased the numbers of endothelial cells in the atheroma expressing the senescence factors p16INK4a and p21, as well as suppressing macrophage infiltration and TNF- α expression in the atheroma, suggesting that vascular aging can be suppressed by HW [ 88 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…During the past decade, many basic and clinical studies have provided evidence supporting the view that H 2 treatment protects against CVD and improves cardiac function. Ohsawa et al discovered that consumption of HW for 6 months reduced the oxidative stress level and the volume of atherosclerotic lesions derived from macrophage accumulation in apolipoprotein E knockout mice (ApoE-/- mice) [ 87 ]. Iketani et al recently revealed that continuous administration of HW in low-density lipoprotein (LDL) receptor-deficient mice decreased the numbers of endothelial cells in the atheroma expressing the senescence factors p16INK4a and p21, as well as suppressing macrophage infiltration and TNF- α expression in the atheroma, suggesting that vascular aging can be suppressed by HW [ 88 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…However, excessive inflammation driven by the inflammasome and IL-1β signaling pathways promotes breast cancer, fibrosarcoma, gastric cancer, and lung metastasis in a context-dependent manner [ 48 ]. Some literature has shown that H 2 can be involved in various models of inflammation based on mechanisms of mitochondrial oxidation inhibition and NLRP3 inflammasome activation ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Effects Of H 2 On Inflammation and Itsmentioning
confidence: 99%
“…NLRP3 plays an important role in the inflammatory response, which may lead to vascular endothelial cell damage and disruption of the blood-brain barrier (BBB). Zhuang et al examined the effects of H 2 gas inhalation in a rat model of SAH [ 21 ]. SAH upregulated the expression of NLRP3 and ASC, accompanied by an increase in inflammatory and apoptotic markers.…”
Section: Effects Of H 2 On Inflammation and Itsmentioning
confidence: 99%
See 2 more Smart Citations